THE INITIAL FULL OUTLINE OF UNRESPONSIVNESS SCORE AS THE PREDICTOR OF CLINICAL OUTCOME IN ACUTE INTRACEREBRAL HEMORRHAGE WITHIN 30 DAYS OF ONSET - Yuliani, Andina; Haryono, Yudha (International Journal of Psychosocial Rehabilitation, 2020)
Background: Intracerebral hemorrhage (IH) is the most leading cause of death and disability due to the inavaibility of adequate therapy, thus regarded as an emergency medical condition to determine the prognosis in patients with IH.Objective: To introduce the Initial Full Outline of Unresponsiveness FOUR score as a clinical scale alternative used in patients with IH with or without loss of consciousness.Methods: The prospective cohort study was conducted in 64 patients with acute IH who visited the emergency unit of Dr. Soetomo Teaching Hospital. It was a clinical neurological test, laboratory test, and head CT scan without contrast. Four scale measurements were conducted during the first visit and its clinical outcomes with the Glasgow Outcome Scale (GOS) within 30 days of onset. A Chi Square test was conducted to discern the correlation between the initial FOUR score and clinical outcomes within 30 days of intracerebral hemorrhage onset.Results: There was a significant correlation between the variables of the FOUR score and clinical outcomes in patients with intracerebral hemorrhage, with a p value of 0.000 (